2017
DOI: 10.1590/1809-4430-eng.agric.v37n6p1126-1136/2017
|View full text |Cite
|
Sign up to set email alerts
|

Peanut Cultivars Submitted to Irrigation Levels and Nitrogen Adubation in Tropical Climate

Abstract: ABSTRACT:The objective of this study was to define the best irrigation level in a sprinkler system, submitted to nitrogen doses in covering in the municipality of Tangará da Serra -MT, for two cultivars of peanut (Arachis hypogaea L.). The experiment was carried out in the experimental field of the State University of Mato Grosso (UNEMAT), located geographically in latitude 14º39'S; Longitude 57º25'W, at 440 meters of altitude. The climate is classified as tropical humid megathermal (Aw), with annual average r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…According to Nakagawa and Rosolem (2011), peanut sensitivity to water stress is lower in the period from seedling emergence to early formation of the floral organs and expressively increases during the flowering and fruiting stages, which occurred in the treatments with deficit irrigation for both sowing dates. These results also corroborate those observed by Barbieri et al (2017), who found differences in the yields of the cultivars IAC Tatu (erect) and Runner IAC 886 (dwarf) under water replacement levels.…”
Section: Discussionsupporting
confidence: 91%
“…According to Nakagawa and Rosolem (2011), peanut sensitivity to water stress is lower in the period from seedling emergence to early formation of the floral organs and expressively increases during the flowering and fruiting stages, which occurred in the treatments with deficit irrigation for both sowing dates. These results also corroborate those observed by Barbieri et al (2017), who found differences in the yields of the cultivars IAC Tatu (erect) and Runner IAC 886 (dwarf) under water replacement levels.…”
Section: Discussionsupporting
confidence: 91%
“…Kandil et al (2007) founded that the nitrogen level was increased stems, leaves number, total pods, and pod dry weight in per plant. Barbieri et al (2017) stated that the treatments of ET0 as 30% and 70% of the allowed more growth as height, but small productivity. Chung et al (1997) found that water deficits reduce the number of leaves per plant, leaf areas and leaf weight.…”
Section: Agronomic Characteristics Of Peanut Plantmentioning
confidence: 99%
“…Wen et al (2001) reported that the maximum recommendable amount of nitrogen was 120 kg N ha -1 for the sandy soil condition in Japan. Barbieri et al (2017) designed an experiment that 4 evapotranspiration levels (30,70,110 and 150%,ET0) and different nitrogen doses (0, 30, 60, 90 and 120 kg/ha) were studied with two peanut varieties in Brazil. Irrigation stages were 110% of ET0.…”
Section: Introductionmentioning
confidence: 99%
“…A maior produtividade dos sistemas irrigados frente aos cultivos de sequeiro é indiscutível. Entretanto, pensando em produtividades econômicas, curvas de respostas são essenciais na tomada de decisão sobre a quantidade de insumo a ser aplicada (BARBIERI et al, 2017). Desta forma, o objetivo deste trabalho foi avaliar a produtividade do amendoim submetido a diferentes lâminas de irrigação e sistemas de preparo do solo.…”
Section: Introductionunclassified